PENYULlNGAN KULIT MASOI (Cinnamomum zanthoneuron BL.) BAGIAN II (Distillation of Maosi bark (Cinnamomum xanthoneuron BL.,). PART II) SIFAT FISIKO KIMIA MINYAK KULlT MASOI BASIL PENYULINGAN CARA KOHOBASI - Bambang Wiyonot; Abdul Hakim Lukman; Poedji Hastoeti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The purpose of this research is to study the physico chemical properties of oil produced from hydrodistillation of massoi bark. The distillation period were varied from 12 to 18, 2 4, 30, and 30 and 36 hours,The result indicates that distillation r appears to have highly significant , affect on oil yield and acid number as shown by linear regresison of respectively Y = 2.132 + 0. 350 X (r = 0. 943) for oil yield and Y = 3.598 + 0.219 X (r = 0.977) for acid number. Besides that massoi bark oil from Maluku has higher eugenol content composed with that from lriqn and West Australia.